A Defense of “Author’s Mouthpiece” - Murphy, David J. (Peitho. Examina Antiqua, 2024)
Against the assumption that their literary form precludes Plato from expressing views in his dialogues, this paper argues that it is legitimate to read certain utterances of characters also as expressions of Plato’s views or to infer Plato’s views from his characters’ speech. Ancient hermeneutical practice, including the practice of Plato’s characters themselves, shows mimetic literature’s reception as “double speech” on two registers, a story register and a rhetorical register. Although aware of the distinction between character and author, ancient readers attribute ideology in characters’ speeches directly to the author. Plato’s contemporaries did this with his dialogues. This practice creates the presumption that philosophical dialogues began as a genre both mimetic and assertoric. Evidence from Cicero and Plutarch supports this presumption, and modern examples show writers and artists weaving ideology into their works. Distinctions in modern literary theory help posit “mouthpiece” as a formal property of characters, “turned on” in order for the author to convey ideology at places in the work. I argue that the “mouthpiece” assumption does not entail fallacy and that the theoretical gains of the “author’s mouthpiece” construct outweigh its risks. Without vitiating dialogues’ status as fiction, the “mouthpiece” assumption serves the history of philosophy and enriches our engagement with the texts.